Consumption-Based Interest Rate and the Present-Value Model of the Current Account-Evidence from Nigeria - Adedeji, Olumuyiwa (Washington, D.C. : International Monetary Fund, 2001)
This paper presents a model of current account determination, based upon the permanent-income hypothesis. A present-value relationship among the current account, changes in net output, the exchange rate and the terms of trade is derived and the implications of such a relationship are tested using data for Nigeria during 1960-97. This paper presents a model of current account determination, based upon the permanent-income hypothesis. A present-value relationship among the current account, changes in net output, the exchange rate and the terms of trade is derived and the implications of such a relationship are tested using data for Nigeria during 1960-97.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet